"Confirmation of Meriones libycus (Rodentia; Gerbillidae) as the Main Reservoir Host of Zoonotic Cutaneous Leishmaniasis in Arsanjan, Fars Province, South of Iran (1999-2000)" - Y Rassi; M Jalali; E Javadian; MH Moatazedian (Tehran University of Medical Sciences, 2001)
This study was carried out in Arsanjan county Fars province, a new focus of ZCL, during 1999-2000. Totally fifty nine Meriones libycus captured by live traps and four out of them (6.8%) were naturally infected with parasites. Parasites were cultured in monophasic medium RPMI 1640 and isolated promastigotes were identified using RAPD-PCR test in Medical Parasitology Unit of Shiraz University of Medical Sciences. The results showed that parasites were L. major, so, Meriones libycus was known the principal reservoir of ZCL in the rural region of Arsanjan. Rhombomys opimus and Tatera indica were absent in the study areas.